Post-translational glycosylation of the contact site A protein of Dictyostelium discoideum is important for stability but not for its function in cell adhesion - Hohmann, Hans-Peter (1987)
The functions of type 1 and 2 carbohydrates of the contact site A (csA) glycoprotein of Dictyostelium discoideum have been investigated using mutants lacking type 2 carbohydrate. In two mutant strains, HG220 and HG701, a 68-kd glycoprotein was synthesized as the final product of csA biosynthesis. This glycoprotein accumulated to a much lower extent on the surfaces of mutant cells than the mature 80-kd glycoprotein did in wild-type cells. There was also no accumulation of the 68-kd glycoprotein observed within the mutant cells nor was a precursor of lower molecular mass detected, in accordance with previous findings that indicated cotranslational linkage of type 1 carbohydrate by N-glycosylation. Pulse-chase labelling showed that a 50-kd glycopeptide was cleaved off from the mutant 68-kd glycoprotein and released into the medium, while the fully glycosylated 80-kd glycoprotein of the wild type was stable. These results assign a function to type 2 carbohydrate in protecting the cell-surface-exposed csA glycoprotein against proteolytic cleavage. HG220 cells were still capable of forming EDTA-stable contacts to a reduced extent, consistent with the low amounts of the 68-kd glycoprotein present on their surfaces. Thus type 1 rather than type 2 carbohydrate appears to be directly involved in intercellular adhesion that is mediated by the csA glycoprotein. Tunicamycin-treated wild-type and mutant cells produce a 53-kd protein that lacks both type 1 and 2 carbohydrates. While this protein is stable and not transported to the cell surface in the wild type, it is cleaved in the mutants and fragments of it are released into the extracellular medium. These results suggest that the primary defect in the two mutants studied is relief from a restriction in protein transport to the cell surface, and that the defect in type 2 glycosylation is secondary.